Knowledge and Practices on Use of Medical Technological Devices Among Nurses in Specialized Hospital (Journal of Preventive and Social Medicine, 2025)
Background: Nurses are more involve handling medical technological devices which is essential for cardiac treatment. There has been no published systematic review which has examined nurses’ Knowledge and practices on use of medical technological devices. To find out the level of Knowledge and practices on use of medical technological devices among nurses in specialized hospital. Methods: A descriptive type of cross-sectional study was conducted from January to December 2023 at National Institute of Cardiovascular Diseases and Hospital (NICVD), Dhaka, Bangladesh. Pretested self-administered questionnaire with Knowledge score; out of 30 questions and practice score; out of 24 questions and observational checklist also used. Score value awarded for wrong answer (0) and correct answer (1). A total of 230 nurses who fulfill the inclusion criteria were selected from different unit of hospital by using simple random sampling techniques. Result: The mean(±SD) age of the respondents was 35.45(±8.27) years. Among 230 respondents around one fifth of respondents had training and majority nurses did not receive any kind of training, consequently it was found that around one fourth of the respondents had low practice level and around one fifth nurses had extremely low knowledge. About one third nurses were used cleaners containing acetone to clean cardiac monitor. All over two third of respondents was correct practice on “Low Battery" warning of a defibrillator. The statistically significant associations were observed between both the duration of working experience in NICVD and the practice level (p= 0.017) Knowledge level (p < 0.0001) as well as the professional education and their practice level (p < 0.0001). A statistically significant correlations were found between knowledge and practice (r =.461**, p < 0.0001). Mann- Whitney U Test indicate that training influenced on knowledge and practice (p < 0.0001). Conclusion: Nurses need adequate training on medical technological devices that will enhance their practical skills.JOPSOM 2023; 42(2): 12-17